Relationship of serum phosphorus level with acute cerebrovascular disease - Sami Ataman; Abdullah Sadık Girişgin; Mustafa Kürşat Ayranci; Kadir Küçükceran (Scientific Reports)
Abstract There are no sufficient studies on laboratory parameters associated with acute stroke. Laboratory parameters associated with acute stroke may become important in the prevention or follow-up of the disease. To investigate the relationship between cerebrovascular disease (CVD) and serum phosphorus levels. This study was conducted prospectively to evaluate the relationship between cerebrovascular disease and phosphorus in patients who applied to the Emergency Medicine Clinic of the Faculty of Medicine Hospital and underwent central imaging between March 1, 2023, and December 31, 2023. 299 patients who applied to the university emergency department were prospectively included in the study with brain computed tomography (CT) and diffusion magnetic resonance imaging (MRI). The lactate, white blood cell, hgb, neutrophil, lymphocyte, urea, creatine and phosphorus values ​​of the patients at their first admission were recorded. The patients were divided into two groups: CVD group and control group. The laboratory parameters of the patients were compared according to the groups. In the ROC analysis performed to evaluate the power of laboratory parameters in predicting the diagnosis of CVD, the AUC value of phosphorus was obtained as 0.935, lactate as 0.620 and urea as 0.596. The optimum cut-off value for phosphorus was calculated as 3.47 (mg/dl) and the sensitivity of this cut-off value was found to be 89%, specifically 86.9%, positive predictive value (ppv) as 77.4% and negative predictive value (npv) as 94%. Lactate, urea and phosphorus values were found to be significantly higher in the CVD group compared to the control group. With this study, we found that serum phosphorus levels were higher than our cut-off value in patients with acute ischemic CVD. We believe that serum phosphorus level will be useful in excluding acute cerebrovascular disease due to its high negative predictive value when evaluated according to the cut-off value of 3.47 (mg/dl).